Future Prospect Versus Past Performance Menjelang Pemilihan Umum tahun 2024 - Indahwati, Indahwati; Agustini , Ni Ketut Yulia (Penerbit Goodwood, 2024)
Purpose: This study aims to determine whether what investors actually expect between future prospects or past performance is related to the certainty and policy of market rules and the upcoming government to provide an overview of decision-making for management and investors. Research methodology: The research variables in this study were operational decisions, strategic decisions, financial performance, and company value as proxies for future prospects and past performance. Factor analysis and multiple linear regression were used for analysis. The population in this study includes companies listed on the Indonesia Stock Exchange. The sample was obtained using the purposive sampling method with the criteria of companies in the industry that were directly affected by the election on a quarterly basis, namely the 3rd and 4th quarters of 2023, and as many as 49 companies with 69 analysis units were obtained. Results: The results show that the three variables–operational decisions (DSO), strategic decisions (growth), and financial performance (ROA)–have a significant effect on the company's value (P/E) ahead of the 2024 elections. Research implications: Investors look more at future prospects by examining operational decisions, strategic decisions, and the company's financial performance. Limitations: The lack of data and the analysis techniques used were very simple. Contributions: This study reveals how operational, strategic, and financial performance decisions affect the value of companies in Indonesia ahead of the 2024 elections. Using regression analysis, this study identifies key factors such as Days Sales Outstanding (DSO), growth (growth), and Return on Assets (ROA) as determinants of company value. These findings provide practical insights for managers and investors, as well as theoretical contributions, by adding the political economy context to the analysis of company values.